Towards Constraining Glacial Isostatic Adjustment in Greenland Using ICESat and GPS Observations - Karina Nielsen; Louise S. Sørensen; Shfaqat Abbas Khan; Sebastian B. Simonsen; René Forsberg; SPADA, GIORGIO (Springer Berlin Heidelberg, 2014)
Constraining glacial isostatic adjustment (GIA) i.e. the Earth’s viscoelastic response to past ice changes, is an important task, because GIA is a significant correction in gravity-based ice sheet mass balance estimates. Here, we investigate how temporal variations in the observed and modeled crustal displacements due to the Earth’s response to ongoing ice mass changes can contribute to the process of constraining GIA. We use mass change grids of the Greenland ice sheet (GrIS) derived from NASA’s high resolution Ice, Cloud and land Elevation Satellite (ICESat) data in three overlapping time spans covering the period 2004–2009 to estimate temporal variations in the elastic response due to present day ice mass loss. The modeled crustal displacements (elastic + GIA) are compared with GPS time series from five permanent sites (KELY, KULU, QAQ1, THU2, and SCOR). We find, that the modeled pattern of elastic crustal displacements shows pronounced variation during the observation period, where an increase in elastic displacement is found at the northwest coast of Greenland, while a decrease is found at the southeast coast. This pattern of temporal changes is supported by the GPS observations. We find, that the temporal behavior of the ICESat-based modeled elastic response agrees well with the GPS observations at the sites KELY, QAQ1, and SCOR. This suggests, that our elastic models are able to resolve the temporal changes in the observed uplift, which indicates that the elastic uplift models are reliable at these sites. Therefore, we conclude that these sites are useful for constraining GIA.